In silicoidentification ofCorynebacterium pseudotuberculosisantigenic targets and application in immunodiagnosis. Issue 6 (June 2016) - Rezende, Andrea de Fátima Silva; Brum, Alexandre Antunes; Reis, Carlos Guilherme; Angelo, Henrique Ramos; Leal, Karen Silva; Silva, Mara Thais de Oliveira; Simionatto, Simone; Azevedo, Vasco; Santos, Anderson; Portela, Ricardo Wagner; Dellagostin, Odir; Borsuk, Sibele
Abstract : N/A: Caseous lymphadenitis (CLA) is a disease caused by Corynebacterium pseudotuberculosis. It affects mainly small ruminants and causes significant economic losses worldwide. Because symptoms are not immediately noticeable, CLA clinical diagnosis is not effective. Numerous serological tests are being developed to detect the disease in asymptomatic animals, but currently available immunoassays have problems with sensitivity. Current ELISA formats use native bacterial antigens, and recombinant proteins could be useful for improving the immunoassay parameters. The C. pseudotuberculosis proteins CP0126a, CP0369 and CP1957 were identified from 2097 candidate proteins by mature epitope density (MED) analysis, expressed in Escherichia coli and evaluated in an indirect immunoenzymic system. The CP0126a, CP0369 and CP1957 ELISAs showed 77.5 %, 92.5 % and 92.5 % specificity and 95 %, 90 % and 85 % sensitivity, respectively. Receiver operating characteristic (ROC) curve analysis showed an area under the curve of 0.874, 0.951 and 0.881, respectively. The proteins identified in silico were recognized by antibodies in the sera from infected animals without being recognized in negative samples. The ELISA assay using the rCP0369 protein as antigen had the greatest specificity and sensitivity values, followed by rCP1957. This is an interesting strategy for seroepidemiological investigations in sheep flocks due to its significant specificity and sensitivity.